2015
DOI: 10.1371/journal.pntd.0004050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Ancestry on INDEL Markers of NFKβ1, CASP8, PAR1, IL4 and CYP19A1 Genes in Leprosy Patients

Abstract: BackgroundLeprosy is an insidious infectious disease caused by the obligate intracellular bacteria Mycobacterium leprae, and host genetic factors can modulate the immune response and generate distinct categories of leprosy susceptibility that are also influenced by genetic ancestry.Methodology/Principal FindingsWe investigated the possible effects of CYP19A1 [rs11575899], NFKβ1 [rs28362491], IL1α [rs3783553], CASP8 [rs3834129], UGT1A1 [rs8175347], PAR1 [rs11267092], CYP2E1 [INDEL 96pb] and IL4 [rs79071878] gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
2
17
1
Order By: Relevance
“…24 Santos et al (2009) described the participation of Europeans (60%), native Indians (28%), and Africans (12%) in the foundation of the city of Belé m. 31 Recent studies have demonstrated that the genetic influence of ethnicity or ancestry might be related to variations in the genes involved in the individual's responses to certain diseases. 25,32 Therefore, the level of ethnic diversity present in the study population may influence the frequency of the CYP2B6 G516T polymorphism compared with different ethnic groups. The frequency of the polymorphic allele previously determined for individuals in the city of Belé m who were receiving treatment for tuberculosis (0.30) is similar to the frequency found in the present study (0.36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Santos et al (2009) described the participation of Europeans (60%), native Indians (28%), and Africans (12%) in the foundation of the city of Belé m. 31 Recent studies have demonstrated that the genetic influence of ethnicity or ancestry might be related to variations in the genes involved in the individual's responses to certain diseases. 25,32 Therefore, the level of ethnic diversity present in the study population may influence the frequency of the CYP2B6 G516T polymorphism compared with different ethnic groups. The frequency of the polymorphic allele previously determined for individuals in the city of Belé m who were receiving treatment for tuberculosis (0.30) is similar to the frequency found in the present study (0.36).…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The Amazon region of Brazil is frequently characterized as an area that shows a variable and sometimes high degree of miscegenation among the Europeans, Africans, and native Indians, 24 a situation that clearly favors the variety of gene expression and the resistance or susceptibility to infectious agents and their associated diseases. 25 The presence of the CYP2B6 G516T polymorphism in HIV-1infected patients may promote the development of adverse reactions associated with antiretroviral agents. These reactions may compromise the treatment protocol in these individuals and cause an increase in the viral load and the selection of viruses with resistance mutations, thus limiting ART options.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in Brazil have also highlighted the importance of the role of ancestry in the susceptibility of a population to disease, including the study of Pinto et al [17], which identified a set of potential genetic markers related to susceptibility to leprosy, influenced in particular by AFR and EUR genomic ancestry. Carvalho et al [33] also found an association between AMR ancestry and an increased risk of developing acute lymphoblastic leukemia in the population of Brazilian Amazonia.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have indicated that populations of different ancestry, in particular AMR, may be relatively more susceptible to certain diseases than other populations [15][16][17][18]. In Mexican and Peruvian populations, for example, AMR ancestry was associated with increased risk for systemic lupus erythematosus [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation